2016
DOI: 10.3109/13880209.2016.1145700
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of the marine macroalgaGelidiella acerosa: identification of active compounds through bioactivity-guided fractionation

Abstract: Context Gelidiella acerosa (Forsskål) Feldmann & G. Hamel (Rhodophyta-Gelidiales) is a marine red macroalga. Our previous work found that a benzene extract of G. acerosa possesses noticeable neuroprotective activity, when evaluated through in vitro and in vivo systems. Objective Bioactive-guided fractionation and identification of active compounds by column chromatography using solvents of varying polarity. Materials and methods Fractionation was done by column chromatography, antioxidant and anticholinesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…Moreover, recent studies from our group revealed that bioactive-guided fractionation revealed the presence of diterpene, phytol, which was further confirmed through molecular docking studies (Syad et al. 2016 ). With this background information, in the present study, the neuroprotective effect of G. acerosa benzene extract was evaluated on Aβ 25–35-treated albino mice.…”
Section: Introductionsupporting
confidence: 57%
“…Moreover, recent studies from our group revealed that bioactive-guided fractionation revealed the presence of diterpene, phytol, which was further confirmed through molecular docking studies (Syad et al. 2016 ). With this background information, in the present study, the neuroprotective effect of G. acerosa benzene extract was evaluated on Aβ 25–35-treated albino mice.…”
Section: Introductionsupporting
confidence: 57%
“…Fucosterol isolated from the marine algae Pelvetia siliquosa and dieckol were also found to reduce oxidative stress in vivo by significantly increasing the free radical scavenging enzyme activities and the activity of hepatic antioxidant enzymes such as glutathione peroxidase and superoxide dismutase [276,277]. Similar anti-cancer and neuroprotective activities have been reported for phytols present in the marine red alga Gelidiella acerosa [284,304].…”
Section: Seaweeds Bioactive Effects: From Pre-clinical To Clinicalmentioning
confidence: 85%
“…Similar results were obtained with Trolox, used as a positive control. Syad et al [22] showed an IC 50 value for phytol of 95.27 μg/mL in the DPPH test. The same research group analysed the potential cholinesterases’ inhibitory activity of this diterpene.…”
Section: Resultsmentioning
confidence: 99%